'n (N.G.) gemeente in "het kamp te Bloemfontein" gedurende die Anglo-Boereoorlog 1900-1903 - Britz, R. M (Faculty of Theology, University of the Free State, 2003)
The two previous editions of Acta Theologica published the stories of the well-known “Tweetoringkerk” and the Dutch Reformed Mission Church of Waaihoek at the time of the Anglo-Boer War (1899-1902). The present article focuses on the third Bloemfontein Dutch Reformed congregation during that war. This congregation came into existence in the concentration camp on the outskirts of the city. It was ministered to by a number of Dutch Reformed clergymen appointed by the new colonial government. The two Lutheran pastors of Bloemfontein (Grosskopf and Arndt) also served the church in the camp. The congregation was structured along the traditional lines of the Dutch Reformed Church: there was a church council, a Sunday school, prayer meetings, a Christian Endeavour Society, and from time to time special evangelisation meetings. Both Baptism and Holy Communion were administered. The available sources reveal that the theological convictions and approach of the ministers who served in the camp relate to the 19th century (Arminian) evangelicalism (and revivals) that were so popular in America and Great Britain. When the war ended and the camp was demolished in January 1903, this first “macro-church” of Bloemfontein also ceased to exist. The article gives an interesting perspective on the religious ministry in a concentration camp during the Anglo-Boer War. Die Anglo-Boereoorlog (1899-1902) het die drie Bloemfonteinse N.G.gemeentes diepgrypend geraak. Hoedat die oorlog op twee hiervan, die Tweetoringkerk en die Sendinggemeente van Waaihoek, ingekom het, is in die vorige uitgawes van Acta Theologica aan die orde gestel.2 Hierdie artikel
Keywords: Anglo-Boer War and the church; Bloemfontein; Concentration Camp; Camp church; Congregation and war; Free State; Revival; Revivalism